Exchanging screen for non-screen sitting time or physical activity might attenuate depression and anxiety: a cross-sectional isotemporal analysis during early pandemics in South America - Sadarangani, Kabir P. (2023)
Objectives: To examine the theoretical substitutions of screen exposure, non-screen sitting time, moderate andvigorous physical activity with depressive and anxiety symptoms in South American adults during the COVID- 19 pandemic. Design: A cross-sectional study during the first months of the COVID-19 pandemic with data from 1981 adults from Chile, Argentina, and Brazil. Methods: Depressive and anxiety symptoms were assessed using the Beck Depression and Anxiety Inventories. Participants also reported physical activity, sitting time, screen exposure, sociodemographic, and tobacco use data. Isotemporal substitution models were created using multivariable linear regression methods. Results: Vigorous physical activity, moderate physical activity, and screen exposure were independently associated with depression and anxiety symptoms. In adjusted isotemporal substitution models, replacing 10 min/day of either screen exposure or non-screen sitting time with any intensity of physical activity was associated with lower levels of depressive symptoms. Improvements in anxiety symptoms were found when reallocating either screen exposure or non-screen sitting time to moderate physical activity. Furthermore, replacing 10 min/day of screen exposure with non-screen sitting time was beneficially associated with anxiety (B = −0.033; 95 % CI = −0.059, −0.006) and depression (B = −0.026; 95 % CI = −0.050, −0.002). Conclusions: Replacement of screen exposure with any intensity of physical activity or non-screen sitting time could improve mental health symptoms. Strategies aiming to reduce depressive and anxiety symptoms highlight physical activity promotion. However, future interventions should explore specific sedentary behaviors as some will relate positively while others negatively.